1990
DOI: 10.1111/j.1528-1157.1990.tb05850.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation in Humans: Neurophysiological Studies and Electrophysiological Monitoring

Abstract: Evidence from studies of experimental animals indicates that electrical stimulation of the vagus nerve alters behavioral and electrographic seizure activity. We report on effects of electrical stimulation of the vagus nerve in five patients with medically intractable seizures as part of a clinical trial of chronic vagal stimulation for control of epilepsy. The mechanism of action of the vagal antiepileptic effect is unknown, and it is hoped that analysis of electrophysiological effects of vagal nerve stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 13 publications
2
20
0
3
Order By: Relevance
“…Epileptic seizures in human cortex, although probably originating from very different causes, have a strikingly similar phenomenology: ensemble bursts extending over large areas of neural tissue (Lopes da Silva et al, 2003). Electrical stimulation has been used in several experimental therapies for epilepsy; stimulation of the vagus nerve is the most well known example (Penfield and Jasper, 1954;Hammond et al, 1995;BenMenachem et al, 1994;Fisher et al, 1997;Handforth et al, 1998;Koo, 2001). Alternatively, animal and modeling studies suggest that focal stimulation at the site of the seizure can terminate seizures after they have started (Lesser et al, 1999;Franaszczuk et al, 2003;Slutzky et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Epileptic seizures in human cortex, although probably originating from very different causes, have a strikingly similar phenomenology: ensemble bursts extending over large areas of neural tissue (Lopes da Silva et al, 2003). Electrical stimulation has been used in several experimental therapies for epilepsy; stimulation of the vagus nerve is the most well known example (Penfield and Jasper, 1954;Hammond et al, 1995;BenMenachem et al, 1994;Fisher et al, 1997;Handforth et al, 1998;Koo, 2001). Alternatively, animal and modeling studies suggest that focal stimulation at the site of the seizure can terminate seizures after they have started (Lesser et al, 1999;Franaszczuk et al, 2003;Slutzky et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, Zabara [79] demonstrated that such stimulation could also infl uence strychnine seizures, again in the dog. This led Terry et al [80] to design a stimulator with fl exible intermittent parameters and an appropriate electrode that was used in an encouraging clinical study in epilepsy [81] . FDA approval was obtained in 1997, and vagal nerve stimulation has become commonplace in epilepsy management.…”
mentioning
confidence: 99%
“…At seizure onset, however, VNS has terminated both the clinical and the EEG seizure activity [32]. At seizure onset, however, VNS has terminated both the clinical and the EEG seizure activity [32].…”
Section: Clinical Studiesmentioning
confidence: 98%